Primary bacterial peritonitis in a previously healthy adolescent female: A case report. (2016) - Blevrakis, Evangelos; Anyfantakis, Dimitrios; Blevrakis, Emmanouil; Vlachakis, Ioannis
Highlights: Primary peritonitis is unusual in immunocompetent parients. Timely diagnosis is crucial. Surgeons must be aware of the condition. Abstract: Introduction: Acute pneumococcal peritonitis represents an unusual entity characterized by infection in the abdominal cavity despite the absence of an obvious causative source. Patients with portal hypertension such as cirrhotics and those with nefrotic syndrome are more frequently encountered in the every day practice. Presentation of case: A 14 years old female was referred to our department by his general practitioner with a 24 h history of right lower abdominal pain and fever. Clinical examination was suggestive for peritonitis and the girl was transferred to the operation room. A diagnosis of primary pneumococcal peritonitis was made on the basis of the findings during surgery and the microbiological tests. Institution of appropriate antibiotics resulted to complete recovery. Discussion: A mini literature review was performed. Conclusion: Primary bacterial peritonitis in adolescents is extremely rare. Surgeons are required to be aware of this entity.